2017
DOI: 10.1186/s12870-017-1044-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of salt tolerance at the seed germination stage in rice

Abstract: BackgroundImproving the salt tolerance of direct-seeding rice at the seed germination stage is a major breeding goal in many Asian rice-growing countries, where seedlings must often establish in soils with a high salt content. Thus, it is important to understand the genetic mechanisms of salt tolerance in rice and to screen for germplasm with salt tolerance at the seed germination stage. Here, we investigated seven seed germination-related traits under control and salt-stress conditions and conducted a genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
109
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 47 publications
6
109
1
Order By: Relevance
“…Salinity seriously affects rice seed germination and seedling establishment, especially in the directseeding area, leading to a reduction of rice yields (Wang et al 2012b;Shi et al 2017). In this study, the indica landrace WJZ from Yunnan province in China showed a strong capability of seed germination and seedling establishment under high salinity stress.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Salinity seriously affects rice seed germination and seedling establishment, especially in the directseeding area, leading to a reduction of rice yields (Wang et al 2012b;Shi et al 2017). In this study, the indica landrace WJZ from Yunnan province in China showed a strong capability of seed germination and seedling establishment under high salinity stress.…”
Section: Discussionmentioning
confidence: 68%
“…The co-located putative QTLs and associated physical locus in this study compared with previously mapped QTLs of salt tolerance in rice. The main associated QTLs from this study are shown on the left (orange frame and pentagram) and previously identified QTLs for salt tolerance are shown on the right (blue frame) (Dubouzet et al 2003;Wang et al 2011;Wang et al 2012;Wang et al 2012;Vinod et al 2015;Sushma et al 2016;Shi et al 2017;Yu et al 2018). Expression pattern of candidate genes in various developmental stages (a) and response to seed germination and salt stress (b) based on Affymetrix microarray datasets and mRNASeq data from the GENEVESTIGATOR (http://www.genevestigator.com).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Salt tolerance during seed germination is not consistently related to other stages (Johnson et al 1992, Shi et al 2017. To date, few studies aimed at genetically dissect salt tolerance during seed germination in rice.…”
mentioning
confidence: 99%